Coordination of Supply Chains with Competing Manufacturers considering Fairness Concerns - Jie Jian; Yuyao Zhang; Lin Jiang; Jiafu Su (Complexity)
In this study, we examined the contract coordination between manufacturers with peer-induced and distributional fairness concerns. A revenue sharing contract was introduced to coordinate a competitive supply chain, in which the manufacturers have different fairness concerns based on centralized decision-making in terms of fairness neutrality. Then, we constructed two game models—the manufacturer’s peer-induced fairness concern model and the manufacturer’s distributional fairness concern model and analyzed the influence of a revenue sharing contract on the pricing decisions and profit distribution of a competitive supply chain considering fairness concerns. The results show that there is a revenue-sharing contract parameter in both the peer-induced and distributional fairness concerns of manufacturers, which can effectively realize Pareto improvements in a supply chain. Meanwhile, the retail and wholesale prices both decreased with the increase in the revenue-sharing ratio between retailers and manufacturers, and the profits of retailers decreased accordingly, but the overall utility of manufacturers and supply chains improved markedly. Moreover, the coordination condition is closely related to the level of fairness concerns of the manufacturers and the competition intensity between two manufacturers. The sharing contract designed in this study can not only effectively improve the utility of retailers and manufacturers but also enhance the total utility of the channel to ensure that node enterprises have long-term, stable, and cooperative relationships and to strengthen the overall competitiveness of the supply chain.